Implications of Geothermal Project Problem in Perspective of Social Engineering Theory and Development Law in Legal Sociology Discourse - Rosdayana Khairuummah (Epistemik Press, 2020)
This journal discusses geothermal project issues that are reviewed from a legal perspective. In this journal, the theory of development law is used in the sociology of law and social engineering discourse. The case study used in this journal is the construction project of a Geothermal Power Plant in Padarincang, Serang, Banten. Law is considered to be very related to changing society and serves to create public order. However, the case of the Padarincang PLTPB construction contradicts this because it disturbs the ecosystem and allows natural damage to occur. The researcher also reviews the factors of order in development through law.